2022
DOI: 10.3390/ijerph19126970
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19, Long COVID Syndrome, and Mental Health Sequelae in a Mexican Population

Abstract: The COVID-19 pandemic is currently a worldwide threat and concern, not only because of COVID-19 itself but its sequelae. The aim of this study was to evaluate whether a relation between COVID-19, Long COVID, and the prevalence of mental health disorders exist. A total of 203 people from Tabasco were included in this study, answering a survey integrated by three dominions: General and epidemiological data, the DASS-21 test (to determine the presence of signs or symptoms suggestive of depression, anxiety, and/or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…Cluster 3 included many psychological symptoms, which have been reported to occur in 62.3% of COVID-19 cases. It is possible that underlying mental illness may be exacerbated by COVID-19 [18]. Notably, cluster 3 had the highest percentage of leaves of absence in our study.…”
Section: Discussionmentioning
confidence: 61%
“…Cluster 3 included many psychological symptoms, which have been reported to occur in 62.3% of COVID-19 cases. It is possible that underlying mental illness may be exacerbated by COVID-19 [18]. Notably, cluster 3 had the highest percentage of leaves of absence in our study.…”
Section: Discussionmentioning
confidence: 61%
“… 42 , 43 Finally, the higher rate of moderate to severe depressive symptoms, brain fog and self-reported anxiety in PASC corroborate with reports that viral persistence in neural tissue, neuroinflammation and blood–brain barrier dysfunction may underlie the long-term neuropsychiatric sequelae reported in SARS-CoV-2 convalescent individuals after recovery from acute infection. 5 , 19 , 44 , 45 , 46 Furthermore, decreased resilience and impaired homeostatic reserve might be underlying mechanisms linking anxiety and depression with the development of PASC and subacute COVID-19. 47 , 48 It is speculated that increased inflammatory responses and an inadequate adaptation of the hypothalamic–pituitary–adrenal axis to hypocortisolemia after acute SARS-CoV-2 infection may underlie the occurrence of symptoms related to brain fog, post-exertional malaise, and neuropsychiatric symptoms, including anxiety and depression in PASC, 2 , 21 , 49 , 50 which often last the longest in patients with persistent COVID-19 symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps more concerning than the variability of specific symptoms in long-COVID patients is that 83% reported three or more long-COVID symptoms, and 32% reported 10 or more symptoms highlighting the cumulative nature of long COVID (Villalpando et al, 2022). As expected, higher numbers of long-COVID symptoms experienced by patients are associated with greater impairment and reduced quality of life (Han et al, 2022), with one study reporting that long-COVID patients' quality of life score was more than 14 points lower than individuals who had never had COVID-19 (Orrù et al, 2021).…”
Section: Health Effects Of Long Covidmentioning
confidence: 99%
“…A study found that long-COVID patients experience a new onset of anxiety, depression, posttraumatic stress disorder (PTSD), psychosis, and suicidal ideation at higher rates than the general population and, in some instances, even higher than among patients fully recovered from COVID-19 (Lamontagne et al, 2021). The estimates of long-COVID patients with anxiety ranged from 23% to 48% (Badenoch et al, 2022;Premraj et al, 2022;Silva Andrade et al, 2021;Villalpando et al, 2022); depression from 17% to 48% (Magnúsdóttir et al, 2022;Premraj et al, 2022;Rass et al, 2022;Silva Andrade et al, 2021;Villalpando et al, 2022) and PTSD from 10% to 37.5% (Badenoch et al, 2022;Rass et al, 2022;Villalpando et al, 2022), far exceeding trends in other populations. Furthermore, the compounding nature of mental health symptoms also raises concerns for long-COVID patients.…”
Section: Mental Health Effect Of Long Covidmentioning
confidence: 99%
See 1 more Smart Citation